THE EFFECT OF BRAND IMAGE AND FOOD SAFETY ON THE PURCHASE DECISION OF SAMYANG NOODLES PRODUCT TO THE STUDENTS OF FACULTY OF ECONOMICS AND BUSINESS OF UNIVERSITY OF NORTH SUMATRA MEDAN - Khairani Khairani (State Islamic University of North Sumatra Indonesia, 2018)
This research aims to attract and maintain consumer loyalty in purchasing products. This type of research is quantitative research. The praburpose of this research is to know and to analyze the influence of brand image to the purchase decision of Samyang noodle product, the influence of food safety to the purchase decision of Samyang noodle product, the influence of brand image and food safety toward the decision of Samyang noodles product to the students of Faculty of Economics and Business University of North Sumatera Medan. This research uses explanative method. Esplanative research aims to understand why a variable can lead to the emergence of a certain effect or effect. Explanative research also aims to explain the picture of a condition, the characteristics of a phenomenon or object that explains the relationship between variables. The population of this study is all students of Strata-1 Faculty of Economics and Business University of North Sumatra who had bought the product of Samyang noodles. This population is an infinite population (indefinite) because the number of buyers of different products Samyang every day. The sample in this research is 97 students of Faculty of Economics and Business University of North Sumatera Medan by using Lemeshow formula. Sampling technique in this research is non-probability sampling by using incidental sampling. The data collection techniques used in this study are questionnaires and documentation. The results showed partial results, brand image significantly influence purchasing decisions, and food safety have an effect but not significant to purchasing decision. Simultaneously, the result of the research shows that brand image and food safety have significant effect on purchasing decision. Keywords: Brand Image, Food Safety and Purchasing Decisions